The Influence of Politics and Law on the National Education System - Iqbal Fawaidul Muhsinin; Novi Andriani; Fatonah Salfadilah (al-Afkar, Journal For Islamic Studies, 2024)
This research article aims to find out how the relationship between the Political & Legal system and the National Education System in Indonesia. This research uses qualitative research techniques with a normative juridical approach. Data analysis uses a statutory approach and an analytical approach. This study analyzes the juridical implications of laws and regulations in the education system. Based on research results in seeking and implementing a national education system, the Indonesian government has a regulation contained in Article 31 paragraph (3) and paragraph (4) of the 1945 Constitution. The provisions in the Constitution were then followed up in the form of Law Number 20 of the year 2003 concerning the National Education System which is the result of a political consensus. There are at least 5 political influences on education, namely: (a) Politics influences educational activities in creating the values and expectations of citizens as needed by the state, (b) politics influences the education budget, (c) politics influences educational resources such as teacher salaries, infrastructure supporting learning activities, and teacher training, (d) politics influences the schooling system such as school structure, teacher reward systems, and student admissions systems, (e) politics affects the quality of graduates seen from how educational graduates behave politically, culturally, economically and socially.